1936
DOI: 10.1149/1.3498148
|View full text |Cite
|
Sign up to set email alerts
|

Organic Inhibitors of Corrosion

Abstract: unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 134.129.115.40 Downloaded on 2014-06-26 to IP ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 134.129.115.40 Downloaded on 2014-06-26 to IP ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 134.129.115.40 Downloaded on 2014-06-26 to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

1954
1954
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 1 publication
5
37
0
Order By: Relevance
“…Roetheli, and McCarthy (5) wbo studied the effect of quinoline tthiodide on cathodic and anodic polarization of iron and steel in N P 2 S0 4 and concluded that inhibition was cathodic. The same conclusion was reached by Mann who proposed a comprehensive theory of inhibition by organic compounds (33).…”
Section: Theories Of Cathodic Inhibitionsupporting
confidence: 71%
See 4 more Smart Citations
“…Roetheli, and McCarthy (5) wbo studied the effect of quinoline tthiodide on cathodic and anodic polarization of iron and steel in N P 2 S0 4 and concluded that inhibition was cathodic. The same conclusion was reached by Mann who proposed a comprehensive theory of inhibition by organic compounds (33).…”
Section: Theories Of Cathodic Inhibitionsupporting
confidence: 71%
“…Relations that result are similar to those for alhphatic amines Steric effects are operative but are of t ess importance than previously thought (33) Further, such effects ar-nut restricted to cathodic adsorption but influence adsorption in general as sho.,n by studies on char-oal('.4) On the basis of this theory geometrical factors should determine the closeness of packing of the adsorbed film over both anodes and cathodes and consequently affect the inhibitive power Thue, the decrease in inhibition generally observed on substitution of a branched aflmyl chain for a straight one is caused by the methyl group in iso compounds preventing close contact of neighboring adsorbed molecules.…”
Section: Data For Benzyl Amine Are Not Availablesupporting
confidence: 65%
See 3 more Smart Citations